Blood product resuscitation mitigates the effects of aeromedical evacuation after polytrauma. Issue 1 (January 2022) - Wallen, Taylor E.; Singer, Kathleen E.; Morris, Mackenzie C.; Blakeman, Thomas; Stevens-Topie, Sabre M.; Strilka, Richard; Pritts, Timothy A.; Goodman, Michael D.
Abstract : BACKGROUND: The combined injury of traumatic brain injury and hemorrhagic shock has been shown to worsen coagulopathy and systemic inflammation, thereby increasing posttraumatic morbidity and mortality. Aeromedical evacuation to definitive care may exacerbate postinjury morbidity because of the inherent hypobaric hypoxic environment. We hypothesized that blood product resuscitation may mitigate the adverse physiologic effects of postinjury flight. METHODS: An established porcine model of controlled cortical injury was used to induce traumatic brain injury. Intracerebral monitors were placed to record intracranial pressure, brain tissue oxygenation, and cerebral perfusion. Each of the 42 pigs was hemorrhaged to a goal mean arterial pressure of 40 ± 5 mm Hg for 1 hour. Pigs were grouped according to resuscitation strategy used—Lactated Ringer's (LR) or shed whole blood (WB)—then placed in an altitude chamber for 2 hours at ground, 8, 000 ft, or 22, 000 ft, and then observed for 4 hours. Hourly blood samples were analyzed for proinflammatory cytokines and lactate. Internal jugular vein blood flow was monitored continuously for microbubble formation with altitude changes. RESULTS: Cerebral perfusion, tissue oxygenation, and intracranial pressure were unchanged among the six study groups. Venous microbubbles were not observed even with differing altitude or resuscitation strategy. Serum lactate levels from hour 2 of flight to the end of observation were significantly elevated in 22, 000 + LR compared with 8, 000 + LR and 22, 000 + WB. Serum IL-6 levels were significantly elevated in 22, 000 + LR compared with 22, 000 + WB, 8, 000 + LR and ground+LR at hour 1 of observation. Serum tumor necrosis factor-α was significantly elevated at hour 2 of flight in 8, 000 + LR versus ground+LR, and in 22, 000 + LR vs. 22, 000 + WB at hour 1 of observation. Serum IL-1β was significantly elevated hour 1 of flight between 8, 000 + LR and ground+LR. CONCLUSION: Crystalloid resuscitation during aeromedical transport may cause a prolonged lactic acidosis and proinflammatory response that can predispose multiple-injury patients to secondary cellular injury. This physiologic insult may be prevented by using blood product resuscitation strategies. Abstract : The goal of our study was to investigate the role of whole blood resuscitation in mitigating the systemic inflammatory response experienced secondary to TBI at altitude.